Understanding the developmental trajectory of second language acquisition and foreign language teaching and learning using the Model of Domain Learning. (November 2019) - Parkinson, Meghan M.; Dinsmore, Daniel L.
Abstract: This article uses the Model of Domain Learning as a framework to better understand the developmental nature of students' second language acquisition and teaching and learning of foreign languages. This examination includes the development of knowledge, strategies, and interest through the stages of expertise in the MDL – namely acclimation, competence, and proficiency/expertise. What encapsulates knowledge, strategies, and interest in the second language acquisition and previous empirical research that supports these developmental notions are overviewed. Finally, directions for future research and practical implications are discussed in light of the developmental nature of expertise development in second language acquisition and foreign language teaching and learning.